Subclinical hypothyroidism, weight change, and body composition in the elderly: the Cardiovascular Health Study. - Garin, Margaret C; Arnold, Alice M; Lee, Jennifer S; Tracy, Russell P; Cappola, Anne R (J Clin Endocrinol Metab, 2014)
BACKGROUND: Subclinical hypothyroidism is common in the elderly, yet its relationship with weight and body composition is unclear. OBJECTIVE: We examined the relationship between subclinical hypothyroidism and weight change and body composition in older adults. METHODS: A total of 427 subclinically hypothyroid and 2864 euthyroid U.S. individuals ≥65 years old enrolled in the Cardiovascular Health Study and not taking thyroid preparations were included. Analyses of 6-year weight change were performed, compared by thyroid status. A cross-sectional analysis of thyroid status and body composition was performed in a subset of 1276 participants who had dual-energy x-ray absorptiometry scans. Models were risk factor-adjusted and stratified by sex. RESULTS: Overall, participants lost weight during follow-up (-0.38 kg/y in men, -0.37 kg/y in women). Subclinical hypothyroidism, when assessed at a single time point or persisting over 2 years, was not associated with a difference in weight change compared with euthyroidism. Subclinical hypothyroidism was also not associated with differences in lean mass, fat mass, or percent fat compared with euthyroidism. A TSH level 1 mU/L higher within the euthyroid or subclinical hypothyroid range was associated with a 0.51-kg higher baseline weight in women only (P < .001) but not with weight change in either sex. A 1 ng/dL higher free T4 level was associated with lower baseline weight and 0.32 kg/y greater weight loss in women only (P = .003). Baseline weight and weight change did not differ by T3 levels. CONCLUSIONS: Our data do not support a clinically significant impact of subclinical hypothyroidism on weight status in the elderly.
Keywords: Aged; Aged, 80 and over; Asymptomatic Diseases; Body Composition; Body Mass Index; Cohort Studies; Female; Humans; Hypothyroidism; Male; Thyroid Gland; Weight Loss